Saberes e não saberes de diretores: relações intra e interpessoais em ambientes escolares - Silva, Marcela Luiz Corrêa da (2023)
In a socializing school, the goal is to experience “non-violent” relationships, which presupposes the commitment of everyone to the quality of teaching and learning, relinquishing judgements of value in conversations and attitudes. Based on theories and practices of conflict mediation techniques – with a focus on “Nonviolent Communication” – and on Bernard Charlot’s “Relation with knowledge”, there arise inquiries for this research, starting from the question: considering the various communications in the school and intra and interpersonal relationships in their environments, how have school principals constituted their knowledge and lack of knowledge? The objective was to analyze the knowledge and lack of knowledge of principals regarding their intra and interpersonal relationships, with a focus on nonviolent communication in school environments. The data were collected during the participation of 37 principals in the learning lesson called “Communication and Interpersonal Relations” in a School Principal Mentoring Program in the year 2021. Through data analysis, two Constellations emerged: the first one was about Ways of dealing with conflicts and interpersonal relationships in the school environment, and the second one focused on Ways of dealing with intrapersonal (subjective) conflicts. They were both analyzed based on the figures of learning of knowledge-object (theoretical perspective), know-how (practical activity), and know-how-to-be (relating). During the analyses, it was observed that principals aimed to develop nonviolent communication, self-awareness, and reflection on interpersonal and intrapersonal relationships within the school environment, as they know (knowledge-object) that this approach provides a fertile ground for more constructive and less violent dialogues in school. However, even though they know this, they don't always manage to translate this knowledge-object into practical know-how or know-how-to-be. The professionals realize that the absence of knowledge-objects, that is, theoretical aspects, hinder the resolution of problems related to the management team's function. Due to this lack of knowledge, there were feelings of insecurity and fear of assuming a management position, especially among beginners. The know-how-to-be and know-how are related to "leading a school," a knowledge-object that needs to be included in the training of a school administrator because, for some participating principals, leadership is only related to organizing events in work teams, with the focus on bringing the school community together in one place. While this is necessary for a school, school leadership is not limited to this perspective alone. In the accounts, it was heard that, when dealing with their intrapersonal (subjective) conflicts, they tend to transform these difficulties into challenges and, in this way, seek to overcome them. Conflict mediation supports the teaching and learning process of students because it aligns with the objectives of quality education, that is, to foster participative citizens who feel responsible for the development of a fair, supportive, empathetic, and democratic society. It was concluded that the knowledge and implications regarding the quality of interpersonal and intrapersonal relationships are related to the importance of language and various fields of knowledge, such as recognizing better interactions with oneself, others, and the world. This complexity of different educational phenomena can be developed in school spaces.